Case Report: Semaglutide-associated depression: a report of two cases - Li, Jia-Rui; Cao, Jinya; Wei, Jing; Geng, Wenqi (Frontiers in Psychiatry, 2023)
Semaglutide, as a glucagon-like peptide-1 receptor agonist (GLP-1 RA), was approved for glucose control in type 2 diabetes mellitus in 2017 and approved for weight loss in 2021 by the U.S. Food and Drug Administration (FDA). No psychiatric adverse effect associated with semaglutide has been reported so far. Here we report two cases of semaglutide-associated depression. One is a middle-aged man with no previous history of depression who developed depressive symptoms about 1 month after taking semaglutide. The other one is a middle-aged woman with recurrent depressive disorder whose symptoms also recurred about 1 month after semaglutide treatment. Depression was improved or relieved after discontinuation of semaglutide in both cases. Possible psychiatric adverse effects of depression should be taken into consideration when semaglutide is administered to patients.